How does social assistance affect consumption and diets after flooding in Southern Bangladesh? - Roy, Shalini (CGIAR System Organization, 2024)
The southern coast of Bangladesh is highly susceptible to flooding, with climate change exacerbating the frequency and intensity of these events. Households affected by floods often resort to “maladaptive” coping strategies such as reducing expenditures, selling assets, borrowing, and drawing down savings—with possible gendered effects. Globally, social assistance programs such as cash or in-kind transfers have shown promise in supporting resource-poor rural households to better cope with weather shocks associated with climate change. But evidence is limited on how social assistance affects households specifically in the context of flooding in Bangladesh, and even fewer studies differentiate effects by gender.